2022
DOI: 10.1021/acsenergylett.2c00311
|View full text |Cite
|
Sign up to set email alerts
|

Cesium Manganese Bromide Nanocrystal Sensitizers for Broadband Vis-to-NIR Downshifting

Abstract: Simultaneously achieving both broad absorption and sharp emission in the near-infrared (NIR) is challenging. Coupling of an efficient absorber such as lead halide perovskites to lanthanide emissive species is a promising way to meet the demands for visible-to-NIR spectral conversion. However, lead-based perovskite sensitizers suffer from relatively narrow absorption in the visible range, poor stability, and toxicity. Herein, we introduce a downshifting configuration based on lead-free cesium manganese bromide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 86 publications
5
42
0
Order By: Relevance
“…No difference was found in the PLE and PL spectra at various emission and excitation wavelengths, which suggests that the green emission originates from the relaxation of the same excited state. Actually, previous studies have shown that the tetrahedrally coordinated Mn 2+ ions could emit green fluorescence due to the radiative d–d transitions (i.e., from 4 T 1 to the ground state 6 A 1 ). Time-resolved PL (TRPL) signal of the Cs 3 MnI 5 NCs can be well fitted by a single-exponential function at both low and high temperatures (Figure S9), similar to a prior report on Cs 3 MnBr 5 NCs . This result suggests that the radiative transition process from 4 T 1 to the ground state 6 A 1 is not influenced by trap states.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…No difference was found in the PLE and PL spectra at various emission and excitation wavelengths, which suggests that the green emission originates from the relaxation of the same excited state. Actually, previous studies have shown that the tetrahedrally coordinated Mn 2+ ions could emit green fluorescence due to the radiative d–d transitions (i.e., from 4 T 1 to the ground state 6 A 1 ). Time-resolved PL (TRPL) signal of the Cs 3 MnI 5 NCs can be well fitted by a single-exponential function at both low and high temperatures (Figure S9), similar to a prior report on Cs 3 MnBr 5 NCs . This result suggests that the radiative transition process from 4 T 1 to the ground state 6 A 1 is not influenced by trap states.…”
supporting
confidence: 85%
“…We have also recorded TRPL curves of the Cs 3 MnI 5 NCs under different excitation wavelengths (Figure S10). Unlike PL decay kinetics of CsMnBr 3 NCs, no excitation-dependent PL decay lifetime can be observed for our Cs 3 MnI 5 NCs, similar to that of Cs 3 MnBr 5 , indicating that there is no significant delay in populating the low-energy excited state of Mn 2+ before it returns to the ground state.…”
mentioning
confidence: 54%
See 3 more Smart Citations